2020
DOI: 10.15446/revfacmed.v68n3.75817
|View full text |Cite
|
Sign up to set email alerts
|

Changes in anthropometric parameters and physical fitness in older adults after participating in a 16-week physical activity program

Abstract: Introduction: Physical activity is important for achieving healthy aging. Objective: To analyze changes in anthropometric parameters and physical fitness among Chilean older adults after participating in a 16-week physical activity program and to evaluate whether there were differences in relation to their baseline nutritional status or not. Materials and methods: Pre-experimental quantitative study. The study population consisted of 176 older adults (155 women and 21 men) distributed in three groups: normal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
8
0
2
Order By: Relevance
“…In addition, the leading causes of attrition are related to diseases, personal problems, not meeting minimum attendance, or conflicts with the training schedule, while only two studies reported a loss of interest (Marie-Ludivine et al, 2010;Combs et al, 2013). This is relevant since PA workshops based on multi-component training and healthy dance in older people implemented by a government institution reported adherence of 54.6% after 16 weeks of participation (Valdés-Badilla et al, 2020). OCS may be PA strategies with high adherence (average >80%), which could transform them into an opportunity to achieve greater outreach and participation in middle-aged and older people, without postponing the benefits for their health (Bu et al, 2010;Origua Rios et al, 2018;Valdés-Badilla et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the leading causes of attrition are related to diseases, personal problems, not meeting minimum attendance, or conflicts with the training schedule, while only two studies reported a loss of interest (Marie-Ludivine et al, 2010;Combs et al, 2013). This is relevant since PA workshops based on multi-component training and healthy dance in older people implemented by a government institution reported adherence of 54.6% after 16 weeks of participation (Valdés-Badilla et al, 2020). OCS may be PA strategies with high adherence (average >80%), which could transform them into an opportunity to achieve greater outreach and participation in middle-aged and older people, without postponing the benefits for their health (Bu et al, 2010;Origua Rios et al, 2018;Valdés-Badilla et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, young taekwondo practitioners are generally athletes of regional or national level [ 41 , 42 , 43 , 44 ]. Therefore, the aim of the interventions does not seek to favor the health of the participants but rather the sports performance, instead, the older people generally practice physical activity to improve their health status [ 4 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the above, proposing alternative physical activity strategies such as TKD programs for older people, especially for Chilean older women who have high rates of a sedentary lifestyle and overweight/obesity [ 18 , 19 ], can be a viable alternative for at least four reasons: (i) little space is required, which is consistent with the characteristics of Family Health Centers (in Spanish, CESFAM) and Community centers that host physical activity governmental workshops in Chile [ 22 ]; (ii) it requires tiny implementation because a large part of the activities are developed individually and in pairs [ 8 , 14 ]; (iii) low costs required to carry out this type of intervention, which would allow its use in a large population of older people [ 8 ]; and (iv) the variety of technical foundations that allow the use of innumerable combinations of movements, a fact that could generate greater motivation and adherence to training [ 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations